Readiness of adolescents to use genetically modified organisms according to their knowledge and emotional attitude towards GMOs - Stanisław Lachowski (Annals of Agricultural and Environmental Medicine, 2017)
Introduction Agriculture based on genetically modified organisms plays an increasingly important role in feeding the world population, which is evidenced by a considerable growth in the size of land under genetically modified crops (GM). Uncertainty and controversy around GM products are mainly due to the lack of accurate and reliable information, and lack of knowledge concerning the essence of genetic modifications, and the effect of GM food on the human organism, and consequently, a negative emotional attitude towards what is unknown.